MRI vastus lateralis fat fraction predicts loss of ambulation in Duchenne muscular dystrophy. (31st March 2020) - Naarding, Karin J.; Reyngoudt, Harmen; van Zwet, Erik W.; Hooijmans, Melissa T.; Tian, Cuixia; Rybalsky, Irina; Shellenbarger, Karen C.; Le Louër, Julien; Wong, Brenda L.; Carlier, Pierre G.; Kan, Hermien E.; Niks, Erik H.
Abstract : Objective: We studied the potential of quantitative MRI (qMRI) as a surrogate endpoint in Duchenne muscular dystrophy by assessing the additive predictive value of vastus lateralis (VL) fat fraction (FF) to age on loss of ambulation (LoA). Methods: VL FFs were determined on longitudinal Dixon MRI scans from 2 natural history studies in Leiden University Medical Center (LUMC) and Cincinnati Children's Hospital Medical Center (CCHMC). CCHMC included ambulant patients, while LUMC included a mixed ambulant and nonambulant population. We fitted longitudinal VL FF values to a sigmoidal curve using a mixed model with random slope to predict individual trajectories. The additive value of VL FF over age to predict LoA was calculated from a Cox model, yielding a hazard ratio. Results: Eighty-nine MRIs of 19 LUMC and 15 CCHMC patients were included. At similar age, 6-minute walking test distances were smaller and VL FFs were correspondingly higher in LUMC compared to CCHMC patients. Hazard ratio of a percent-point increase in VL FF for the time to LoA was 1.15 for LUMC (95% confidence interval [CI] 1.05–1.26; p = 0.003) and 0.96 for CCHMC (95% CI 0.84–1.10; p = 0.569). Conclusions: The hazard ratio of 1.15 corresponds to a 4.11-fold increase of the instantaneous risk of LoA in patients with a 10% higher VL FF at any age. Although results should be confirmed in a larger cohort with prospective determination of the clinical endpoint, this added predictive value of VL FF to age on LoA supports the use of qMRI FF as an endpoint or stratification tool in clinical trials.